Pembelajaran Berkarakteristik dan Inovatif Abad 21 pada Materi Zat dan Perubahannya Dengan Model PBM Di SMK N 1 Adiwerna - Sustiyowati, Sustiyowati; Sutji, Muljani (Cakrawala: Jurnal Pendidikan, 2022)
Science or PIPAS is one of the branches of science that is important for human life, it is also the basis of science that gave birth to many technological innovations today. There are still some learners who consider the Natural and Social Sciences Project is an elusive science. The difficulty of studying the Natural and Social Sciences Project is because they are less eager to learn how to solve the problems of the Natural and Social Sciences Project. With new problems in the real world, students must have four competencies: critical thinking and problem solving, creativity, communication skills, and the ability to work together or collaborate. One of the factors causing low student learning outcomes is that learning is still teacher-centered. An innovative 21st-century learning model that can improve liveliness, and student learning outcomes is a Problem-Based Learning model. This article aims to study and provide an overview of the characterful and innovative learning models of the 21st century in the subject of the Natural and Social Sciences Project on substance materials and their changes.